1981
DOI: 10.2527/jas1982.5361524x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Digestibility and Performance of Pigs Fed Sorghums Varying in Tannin Concentration

Abstract: Four sorghums, ranging widely in tannin content, and yellow corn were evaluated in two 5 x 5 Latin square digestion trials and a growth trial. All grains were grown in the same field under similar conditions. The sorgums and their tannin contents (milligrams of catechin/100 mg of dry matter, as determined by a modified vanillin-HCl method) were: Ga615, 3.40; NK300, 3.17; TAM680, .83, and G766-W, .88. Diets were supplemented with casein to provide .70 and .60% lysine in digestion trials 1 and 2, respectively. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1
3

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(49 citation statements)
references
References 17 publications
4
41
1
3
Order By: Relevance
“…In addition, acorns provide high amounts of crude fibres (including lignin, above all), resulting in reduced digestibility rate of organic matter and lower expected metabolizable energy of the diet. Feed intake depression from acorns tannins in the diet can be excluded and this finding is in contrast with references [45][46][47][48][49][50][51] Table 2 reports tannins intakes recorded throughout the experimental feeding (one week) for the three groups of animals according to acorns inclusion in the diet (70% vs 50% vs 0%) and entity of parotidomegaly, expressed as percentage of mass increase (70% and 50% acorns combined diets groups) compared to the parotid gland from the control diet (0% acorns combined diets).…”
Section: Daily Feed Intakes and Dietary Tannins Ingestion From Differcontrasting
confidence: 46%
See 1 more Smart Citation
“…In addition, acorns provide high amounts of crude fibres (including lignin, above all), resulting in reduced digestibility rate of organic matter and lower expected metabolizable energy of the diet. Feed intake depression from acorns tannins in the diet can be excluded and this finding is in contrast with references [45][46][47][48][49][50][51] Table 2 reports tannins intakes recorded throughout the experimental feeding (one week) for the three groups of animals according to acorns inclusion in the diet (70% vs 50% vs 0%) and entity of parotidomegaly, expressed as percentage of mass increase (70% and 50% acorns combined diets groups) compared to the parotid gland from the control diet (0% acorns combined diets).…”
Section: Daily Feed Intakes and Dietary Tannins Ingestion From Differcontrasting
confidence: 46%
“…Scientific references report evident correlation between dietary polyphenols rich diets and health enhancing properties: antioxidant properties [11][12][13], antibacterial activity on different bacterial strains in vitro and in vivo [7,[14][15][16][17][18][19][20], antiparasitic [21], antiulcerogenic [22][23][24] antidiarrhoic [25], antimutagenic [26][27][28][29][30][31][32][33], antitumor [34][35][36][37][38], and some neoplastic cell line apoptosis [39,40]. On the other hand, high tannins diets might also result in detrimental effects like hepatotoxicity [41,42], toxic nephrosis [43], oesphageal cancer [44], depression of feed intake and growth rate in many animal species [45][46][47][48][49][50][51].…”
Section: Biological Role Of Polyphenolsmentioning
confidence: 99%
“…This postulation is partly based on evidence from numerous feeding studies that show animals (from rodents to livestock species) fed whole grain sorghum, in particular the slowly digested high tannin sorghum varieties, have reduced weight gain. (116,117,120,154,155) In general, dietary fiber and whole grain intakes have been associated with reduced risks of obesity, overweight and with lowered waist-to-hip ratio. (156,157) Effects of dietary fiber on appetite and satiety have been proposed as major mechanisms for these reductions.…”
Section: Effects On Energy Balancementioning
confidence: 99%
“…Of the common ANFs, trypsin inhibitors (Barth et al 1993;Marty 1993;Schulze 1994), lectins (Schulze 1994) and tannins (Cousins et al 1981;Mitaru et al 1984; have been shown to elevate the amount of endogenous amino acids and nitrogen passing the terminal ileum substantially. Tannins are known to interact with both dietary and endogenous nitrogen in the digestive tract and cause decreased true amino acid digestibilities as well (Jansman 1993).…”
Section: B) Anti-nutritive Factors (Anfs)mentioning
confidence: 99%